2021
DOI: 10.1002/acm2.13074
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Ex Vivo evaluation of an extracorporeal high‐intensity focused ultrasound (HIFU) system

Abstract: Background: High-intensity focused ultrasound (HIFU) has been in clinical use for a variety of solid tumors and cancers. Accurate and reliable calibration is in a great need for clinical applications. An extracorporeal clinical HIFU system applied for the investigational device exemption (IDE) to the Food and Drug Administration (FDA) so that evaluation of its characteristics, performance, and safety was required.Methods: The acoustic pressure and power output was characterized by a fiber optic probe and a rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
(90 reference statements)
2
4
0
Order By: Relevance
“…Our model showed that the temperature of the spheroids was uniform throughout the culture medium with no significant temperature gradient within the focal region. Similar observations were obtained by Zhou et al (53), where the center of the ablated cancer appeared analogous to viable cells after H&E staining. These cells maintained their characteristics of cytologic staining and nuclear chromatin without any signs of breakdown.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our model showed that the temperature of the spheroids was uniform throughout the culture medium with no significant temperature gradient within the focal region. Similar observations were obtained by Zhou et al (53), where the center of the ablated cancer appeared analogous to viable cells after H&E staining. These cells maintained their characteristics of cytologic staining and nuclear chromatin without any signs of breakdown.…”
Section: Discussionsupporting
confidence: 90%
“…These cells maintained their characteristics of cytologic staining and nuclear chromatin without any signs of breakdown. However, electron microscopy revealed that the cytoplasm of those normal-appearing cancer cells contained vacuoles, where the cell membranes were disintegrated with unidentified organelle structures, suggesting an irreversible cell death with the preservation of cellular structure induced by thermal fixation instead of incomplete coagulation necrosis (53). Add to that, the central part of the ablated tumor resisted degradation since the wound-healing process could not extend to this region right after HIFU treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our model showed that the temperature of the spheroids was uniform throughout the culture medium with no significant temperature gradient within the focal region. Similar observations were obtained by Zhou et al [65], where the center of the ablated cancer appeared analogous to viable cells after H&E staining. These cells retained their cytologic staining and nuclear chromatin features with no evidence of deterioration.…”
Section: Model Validationsupporting
confidence: 89%
“…When low ultrasound frequency (within the KHz range) is applied, the cavitation effect dominates, and it can be used to trigger drug release, perfluorocarbon nanoemulsions are used to overcome the limitations of bubble lifetime and extravasation, and to promote cell uptake and/or drug release at the tumor site [ 315 , 316 , 317 ]. Another possibility is to use high-intensity focused ultrasound to increase the temperature, which can also promote drug release [ 318 , 319 , 320 ]. J.L.…”
Section: Stimuli-responsive Nanomaterials For Lymphatic System Drug D...mentioning
confidence: 99%